Rivalitas Politik dan Ideologi antara Dinasti Turki Utsmani dengan Dinasti Safawiyah - Ragil Pangestu; Shabrina Fillah; Ronadia Ronadia; Hudaidah Hudaidah; Risa Marta Yati (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This research explores the political and ideological contestation between the Ottoman and Safavid empires during the 16th and 17th centuries, a period marked as one of the most influential rivalries in the history of the Islamic world. The study’s significance lies in its ability to reveal how theological distinctions between Sunni and Shia doctrines evolved into a struggle for political legitimacy and geopolitical supremacy across the Middle East. Employing the historical research method combined with a descriptive-analytical approach, this study follows the stages of heuristics, source evaluation, interpretation, and historiography to reconstruct objectively the political interactions of both powers based on primary historical evidence. The result demonstrate that events from the battle of chaldiran 1514 to the Treaty of Zuhab 1639 not only represented an ideological confrontation but also reflected strategic maneuvers to preserve power equilibrium. Ultimately, the Ottoman-Safavid confrontation delineated a political and religious boundary that continued to shape the region into the modern era, while the post-Zuhab reconciliation exemplified how diplomacy and rational negotiation could ease tensions between rival Islamic states.